Intestinal Dysbiosis and the Developing Lung: The Role of Toll-Like Receptor 4 in the Gut-Lung Axis - Wedgwood, Stephen; Gerard, Kimberly; Halloran, Katrina; Hanhauser, Ashley; Monacelli, Sveva; Warford, Cris; Thai, Phung N.; Chiamvimonvat, Nipavan; Lakshminrusimha, Satyan; Steinhorn, Robin H.; Underwood, Mark A. (Frontiers in Immunology, 2020)
Background: In extremely premature infants, postnatal growth restriction (PNGR) is common and increases the risk of developing bronchopulmonary dysplasia (BPD) and pulmonary hypertension (PH). Mechanisms by which poor nutrition impacts lung development are unknown, but alterations in the gut microbiota appear to play a role. In a rodent model, PNGR plus hyperoxia causes BPD and PH and increases intestinal Enterobacteriaceae, Gram-negative organisms that stimulate Toll-like receptor 4 (TLR4). We hypothesized that intestinal dysbiosis activates intestinal TLR4 triggering systemic inflammation which impacts lung development. Methods: Rat pups were assigned to litters of 17 (PNGR) or 10 (normal growth) at birth and exposed to room air or 75% oxygen for 14 days. Half of the pups were treated with the TLR4 inhibitor TAK-242 from birth or beginning at day 3. After 14 days, pulmonary arterial pressure was evaluated by echocardiography and hearts were examined for right ventricular hypertrophy (RVH). Lungs and serum samples were analyzed by western blotting and immunohistochemistry. Results: PNGR+hyperoxia increased pulmonary arterial pressure and RVH with trends towards increased plasma IL1β and decreased IκBα, the inhibitor of NFκB, in lung tissue. Treatment with the TLR4 inhibitor attenuated PH and inflammation. Conclusion: PNGR induces an increase in intestinal Enterobacteriaceae leading to PH. Activation of the TLR4 pathway is a promising mechanism by which intestinal dysbiosis impacts the developing lung.